USM DANCE THEATRE 'HANG TUAH AND PUTERI GUNUNG LEDANG' WELL-RECEIVED IN JOGJAKARTA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 24 November 2016 The dance theatre 'Hang Tuah and Puteri Gunung Ledang' which dramatises the love story between two individuals from Malacca (Hang Tuah) and Majapahit (Puteri Gunung Ledang) which ended under the order of the Sultan of Malacca of that period, was wellreceived at the ongoing International Arts Festival 2016 in Jogjakarta, Indonesia.